Actualization of Transformational Leadership based on Spiritual Empowerment for Enhancing Quality of Higher Education - Junaidi, Muhammad; Himmah, Asmi Faiqatul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2019)
ABSTRACT Leadership has significant and strategic role for enhancing the quality of higher education institution. In implementing transformational leadership based on spiritual empowerment, the leadership should have mastered these four components: a) charisma, b) inspirational motivation, c) intellectual stimulation, d) individualized consideration. This article uses descriptive qualitative approach and gets some discoveries as follows; first, IAIN actualyzes the concept of “Islam Nusantara” in constructing academic atmosphere. Second, IAIN actualyzes KH. Shiddiq’s four pillars of spiritual empowerment. Research result showed that the implementation of transformational leadership style has been implemented as follows: First, to fulfill and explore charismatic leadership in IAIN, the principal implemented some steps as follows: First, illustrating vision and mission formulation clearly. Second, foster pride in the institution. Third, respected and appreciated by followers. Forth, needs to gain the support and trust from followers. Second, to express his inspirational motivation to his followers, the principal implemented his ability in communicating high expectation and exploring the symbols/jargon/motto of institution for focusing on the effort to explore them simply. Third, the way principal stimulates his followers intellectual through these following things: 1) promoting intellectual behavior. 2) conducting learning organization. 3) Intellectual sensitivity. Fourth, able to provide appropriate solutions. 4)Individualized Consideration.